Effect of dentin dehydration and composite resin polymerization mode on bond strength of two self-etch adhesives - Pooran Samimi; Mehdi Alizadeh; Farinaz Shirban; Amin Davoodi; Maryam Khoroushi (Wolters Kluwer Medknow Publications, 2016)
Background: Dual-cured composite resins are similar to self-cured composite resins in some of their clinical applications due to inadequate irradiation, lack of irradiation, or delayed irradiation. Therefore, incompatibility with self-etch adhesives (SEAs) should be taken into account with their use. On the other, the extent of dentin dehydration has a great role in the quality of adhesion of these resin materials to dentin. The aim of this study was to investigate the effect of dentin dehydration and composite resin polymerization mode on bond strength of two SEAs. Materials and Methods: A total of 120 dentinal specimens were prepared from extracted intact third molars. Half of the samples were dehydrated in ethanol with increasing concentrations. Then Clearfil SE Bond (CSEB) and Prompt L-Pop (PLP) adhesives were applied in the two groups. Cylindrical composite resin specimens were cured using three polymerization modes: (1) Immediate light-curing, (2) delayed light-curing after 20 min, and (3) self-curing. Bond strength was measured using universal testing machine at a crosshead speed of 1 mm/min. Data were analyzed with two-way ANOVA and Duncan post hoc tests. Statistical significance was defined at P < 0.05. Results: There were no significant differences for CSEB subgroups with hydrated and dehydrated dentin samples between the three different curing modes (P > 0.05). PLP showed significant differences between subgroups with the lowest bond strength in hydrated dentin with delayed light-curing and self-cured mode of polymerization. Conclusion: Within the limitations of this study, a delay in composite resin light-curing or using chemically cured composite resin had a deleterious effect on dentin bond strength of single-step SEAs used in the study.